Réponses

Meilleure réponse !
2014-05-15T20:17:13+02:00
Bonsoir

D=6(x+5)   = 6x +30

E=4y(2y-1)    = 8y² -4y         

F=-2(x²+7)-x(15+7x) =  -2x²  -14 - 15x - 7x² = -9x² -15x -14

G=(x+1)(x+4)  = x² +4x +x +4 = x² +5x +4   
 H=(-4x+2)(4x-3) = - 16x² + 12x +8x - 6 = 16x² + 20x -6


2014-05-15T20:20:10+02:00
D=6(x+5)
  =6*x+6*5
  =6x+30
 
E=4y(2y-1)
   =4y*2y+4y*(-1)
   =8y²-4y
 
F=-2(x²+7)-x(15+7x)
  =-2*x²-2*7-x*15-x*7x
  =-2x²-14-15x-7x²
  =-9x²-15x-14

G=(x+1)(x+4)
  =x*x+x*4+1*x+1*4
  =x²+4x+x+4
  =x²5x+4            

H=(-4x+2)(4x-3)
  =-4x*4x-4x*(-3)+2*4x+2*(-3)
  =-16x²+12x+8x-6
  =-16x²+20x-6

voilà :)